An experimental analysis of mechanical properties for a dissimilar pattern structure in the 3-D printing of a PLA5F filament using the Taguchi method - Thamizh Selvan S; Mohandass M (Materials Research Express)
Many automobile components and machine parts can be fabricated using the Fused Deposition Modeling (FDM) process with materials such as Polylactic Acid (PLA), Acrylonitrile Butadiene Styrene (ABS), Polyethylene Terephthalate Glycol (PET-G), and polymeric composite materials (e.g., PLA with carbon fiber, PLA with glass fiber). In this study, a new polymeric composite material was fabricated using Polylactic Acid and natural flax fiber was analysed for tensile stress, elongation, and impact load resistance using Taguchi Analysis. This analysis optimized the printing parameters, including layer thickness (0.15, 0.25, 0.35 mm), nozzle movement speed (80, 100, 120 mm s ^−1 ), filling structure (Lines - a, Triangular - b, and Octet - c), and occupancy rate (20%, 40%, 60%). The American Society for Testing and Materials (ASTM) standards for tensile strength (ASTM D638) and impact strength (ASTM D256) were used for evaluation. As a result, layer thickness was found to be the most effective variable for improving tensile characteristics, compared to extruder temperature, occupancy rate, or filling structure pattern. Mechanical properties including a layer thickness of 0.25 mm, an occupancy ratio of 20% for the bottom of the 2nd layer and 40% for the top of the 4th layer, triangular and octet filling structures, a nozzle speed of 100 mm s ^−1 , and an extruder temperature of 200 °C are considered the most appropriate parameters for producing automotive parts in Three Dimensional (3D) Printing. Due to its tensile properties and impact strength resistance, these settings can be utilized in potential application in a wide variety of machine parts and vehicle components.